2017
DOI: 10.12816/0039063
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Foot Awareness among Diabetic Patients in Saudi Arabia

Abstract: Aim of the work: diabetic foot disease(DFD) is diabetic patient's foot affection by ulcers which are accompanied by peripheral vascular disease and/or diabetic neuropathy of the lower limb. Prevalence of diabetic ulcer is ranging from 2%-10%. High rate of lower limb amputation in DFD (More than 15%) and survival rate for undertaken amputation patient are short. Ninety diabetic amputations are performed monthly in Saudi Arabia capital of Riyadh. Identification of DFD and diabetic patient's awareness of DFD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 5 publications
3
17
1
Order By: Relevance
“…The majority of subjects had adequate knowledge about the complications of the diabetic feet diseases and this was constituent with the study of Al-Hariri (17) in Al-Dammam City, KSA where a good and favorable knowledge was present among the most of the diabetic patients toward the diabetic foot care and complications. The same results indicated a good knowledge about diabetic foot care and complications was found among the diabetic subjects in primary health care facilities in KSA (21) . However, in South Africa, the awareness of participants about the diabetic foot complications was suboptimal among most of the participants (22) .…”
Section: Discussionsupporting
confidence: 66%
“…The majority of subjects had adequate knowledge about the complications of the diabetic feet diseases and this was constituent with the study of Al-Hariri (17) in Al-Dammam City, KSA where a good and favorable knowledge was present among the most of the diabetic patients toward the diabetic foot care and complications. The same results indicated a good knowledge about diabetic foot care and complications was found among the diabetic subjects in primary health care facilities in KSA (21) . However, in South Africa, the awareness of participants about the diabetic foot complications was suboptimal among most of the participants (22) .…”
Section: Discussionsupporting
confidence: 66%
“…Data collection was done by the investigator using a structured questionnaire in the Arabic language. The set of closed type questions were developed from the literature review of similar objectives[1011121314151617] and were tested for its reliability and validity with a Cronbach's alpha 0.86. The questionnaire contained three parts: (1) demographic profile of the patients, (2) six questions on knowledge and seven questions on attitude toward diabetic foot care, and (3) eight questions on the practice of diabetic foot care.…”
Section: Methodsmentioning
confidence: 99%
“…A study showed that a large number (>50%) of diabetic patients were found to have poor knowledge of diabetic foot care. [1314] Those who had a higher level of education and who were less than 65-year old had a significantly better score for previous foot care education. [12] Other studies have shown that only 13.3% of the study participants have good knowledge of diabetic foot care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) Sub-Theme 2 concept map prevention and management of diabetic foot car Concept maps are also useful in highlighting some of the preventive strategies that diabetic patients can utilize to cushion themselves against the risk of developing diabetic foot ulcerations. [21] asserts that broad concepts map highlight preventive measures that enlighten patients such as nail and skin care, blood pressure control, and lifestyle modification. For instance, in nail and skin care, concepts maps offer standard guidelines that inculcate patients the different ways that they can be able to maintain the integrity of their skin [18].…”
Section: Theme 2 Concept Mapping In Health Educationmentioning
confidence: 99%